EVALUASI PENYUSUNAN ANGGARAN PENJUALAN PADA BIDANG ANGKUTAN DALAM - zainab zainab (Jurnal Ekonomi dan Kewirausahaan Kreatif, 2019)
This study aims to evaluate preparation of a sales budget in the field of inner transportation. Budgeting is the company refers to the companies RKAP, in this case it refers to the USD exchange rate, inflation rate, loan interest rest and dividend distribution in effect in the year the RKAP was made. The advantages of this company budgeting are 1) already have a standard in its use 2) the budget drafting section has discussed in each sector for budget allocation 3) the complier already has assumptions or trends that occur at the time the budget is effective. Keywords : Sales budget, Management planning and control